Performance Comparison of Pure and Modified Sine Wave Inverters in an Off-Grid PV System - Nelly Safitri; Rudi Syahputra; Supri Hardi; Saifuddin Muhammad Jalil (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study evaluates the performance of Pure Sine Wave (PSW) and Modified Sine Wave (MSW) inverters within small-scale off-grid solar power generation systems. The assessment was conducted utilizing a 160 Wp monocrystalline solar panel, a 10 A solar charge controller (SCC), a 12.8 V–100 Ah lithium iron phosphate (LiFePO₄) battery, along with both 500 W PSW and MSW inverters, across varying panel tilt angles ranging from 45°-165°. The findings indicated that the PSW inverter delivered a more consistent output voltage between 221 and 222 V, exhibiting minimal fluctuation of ±1 V and low harmonic distortion at 2.5%. The MSW inverter produced an output voltage between 222 and 225.5 V, characterized by greater variability and higher harmonic distortion under both light and heavy load conditions. The analysis of the solar photovoltaic (PV) system provides critical insights into the performance differences between the two inverter types. Notably, the results related to tilt angle are not merely supplementary; they serve as indicators of varying irradiance conditions, enabling a more comprehensive evaluation of inverter performance concerning fluctuations in input power levels. Both PSW and MSW inverters achieved an efficiency rating of 85%, ensuring stable and smooth outputs. However, with regard to long-term reliability, the PSW inverter significantly surpasses its counterpart, rendering it a more appropriate choice for permanent solar PV installations. As the results, the PSW inverter is particularly suited for sensitive loads that demand high power quality, while the MSW inverter remains viable for less demanding applications when the cost is considered.